Translation of English Fiction and Drama in Modern China: Social Context, Literary Trends, and Impact - Fan, Shouyi (Meta, 1999)
AbstractThis article, which is organized along a chronological-thematic framework, will briefly review the early days of translating American and British fiction and drama into Chinese, the social context in which these translations were done, the literary ideas which have affected the work of Chinese writers, and the social impact that translated works of literature and literary theory have had in various periods of literature. The bottom line is that the literary works introduced to China to date represent only the tip of the iceberg. We need more quality translations for Chinese readers and more qualified and experienced translators to complete the job.